A steeply-inclined trajectory for the Chicxulub impact - Collins,G; Patel,N; Davison,T; Rae,A; Morgan,J; Gulick,S; IODPICDP,Expedition 364 & Third-Party Scientists (Nature Communications, 2020)
The environmental severity of large impacts on Earth is influenced by their impact trajectory. Impact direction and angle to the target plane affect the volume and depth of origin of vaporized target, as well as the trajectories of ejected material. The asteroid impact that formed the 66 Ma Chicxulub crater had a profound and catastrophic effect on Earth’s environment,but the impact trajectory is debated. Here we show that impact angle and direction can be diagnosed by asymmetries in the subsurface structure of the Chicxulub crater. Comparison of 3D numerical simulations of Chicxulub-scale impacts with geophysical observations suggests that the Chicxulub crater was formed by a steeply-inclined (45 -60° to horizontal) impact from the northeast; several lines of evidence rule out a low angle (< 30°) impact. Asteeply-inclined impact produces a nearly symmetric distribution of ejected rock and releases more climate-changing gases per impactor mass than either a very shallow or near-vertical impact.